The prognostic value of testicular microlithiasis as an incidental finding for the risk of testicular malignancy in children and the adult population: A systematic review. On behalf of the EAU pediatric urology guidelines panel. Issue 6 (December 2021) - 't Hoen, Lisette A.; Bhatt, Nikita R.; Radmayr, Christian; Dogan, Hasan S.; Nijman, Rien J.M.; Quaedackers, Josine; Rawashdeh, Yazan F.; Silay, Mesrur S.; Tekgul, Serdar; Stein, Raimund; Bogaert, Guy
Summary: Introduction: The exact correlation of testicular microlithiasis (TM) with benign and malignant conditions remains unknown, especially in the paediatric population. The potential association of TM with testicular malignancy in adulthood has led to controversy regarding management and follow-up. Objective: To determine the prognostic importance of TM in children in correlation to the risk of testicular malignancy or infertility and compare the differences between the paediatric and adult population. Study design: We performed a literature review of the Medline, Embase and Cochrane controlled trials databases until November 2020 according to the Preferred Reporting Items of Systematic Reviews and Meta-Analyses (PRISMA) Statement. Twenty-six publications were included in the analysis. Results: During the follow-up of 595 children with TM only one patient with TM developed a testicular malignancy during puberty. In the other 594 no testicular malignancy was found, even in the presence of risk factors. In the adult population, an increased risk for testicular malignancy in the presence of TM was found in patients with history of cryptorchidism (6% vs 0%), testicular malignancy (22% vs 2%) or sub/infertility (11–23% vs 1.7%) compared to TM-free. The difference between paediatric and adult population might be explained by the short duration of follow-up, varying between six months and three years. With an average age at inclusion of 10 years and testicular malignancies are expected to develop from puberty on, testicular malignancies might not yet have developed. Conclusion: TM is a common incidental finding that does not seem to be associated with testicular malignancy during childhood, but in the presence of risk factors is associated with testicular malignancy in the adult population. Routine monthly self-examination of the testes is recommended in children with contributing risk factors from puberty onwards. When TM is still present during transition to adulthood a more intensive follow-up could be considered.